2021
DOI: 10.1016/j.celrep.2021.109572
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic modulation of dentate gyrus processing through dynamic reconfiguration of inhibitory circuits

Abstract: Highlights d Optogenetic release of ACh in the DG increases responses of GCs to afferent inputs d Increased GCs responses are due to a nicotinic-dependent perisomatic disinhibition d Disinhibition induced by ACh is due to a decreased participation of PV interneurons d Coincident activation of afferent inputs and ACh release induce plasticity in GCs

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 85 publications
(95 reference statements)
1
8
0
Order By: Relevance
“…Interestingly, a significant increase was observed in the density of c-Fos+ GCs (Figure 8F and 8G). This finding is consistent with recent reports that stimulating cholinergic afferents lowed the threshold for GC firing thus making them more excitable, potentially through interneuron-mediated disinhibition (Martinello et al, 2015; Ogando et al, 2021). By contrast, no significant difference was observed in the density of c-Fos+ GluR2/3+ MCs (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Interestingly, a significant increase was observed in the density of c-Fos+ GCs (Figure 8F and 8G). This finding is consistent with recent reports that stimulating cholinergic afferents lowed the threshold for GC firing thus making them more excitable, potentially through interneuron-mediated disinhibition (Martinello et al, 2015; Ogando et al, 2021). By contrast, no significant difference was observed in the density of c-Fos+ GluR2/3+ MCs (Fig.…”
Section: Resultssupporting
confidence: 93%
“…To fill these knowledge gaps, our study demonstrated that activation of DB-DG cholinergic projections promotes quiescent rNSC activation and spatial memory. In addition, most studies on cholinergic modulation of the DG were performed using slice electrophysiology (Martinello et al ., 2015; Ogando et al ., 2021; Pabst et al ., 2016). Although these studies have undoubtedly provided valuable information on cholinergic regulation of specific types of DG cells, cell-type-specific signaling mechanisms underlying cholinergic activity-dependent modulation of DG is largely lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we think that both subthreshold and Hebbian LTP cannot be practically induced without reduction of GABAergic inputs. Recently, it was reported that disinhibition is induced at MPP-GC synapses by septal acetylcholine release [ 38 ], whereas it is unknown whether similar disinhibition occurs at LPP-GC synapses. It remains to be elucidated whether Hebbian LTP can be induced when feedforward GABAergic inputs are inhibited under an influence of neuromodulator.…”
Section: Discussionmentioning
confidence: 99%
“…A decline of the projections from the MS to the DG during aging has been previously described 15 . These cholinergic projections from the MS target both GCs and hilar interneurons, including NPY/SST-containing HIPP cells and parvalbuminergic basket cells, and axo-axonic cells 37 . HIPP cells are vulnerable to a cholinergic decline 27 and mediate cholinergic-induced NPY-Y1 receptor stimulation at the DG GCs 7 .…”
Section: Discussionmentioning
confidence: 99%